Edward Goldsmith’s Criticism of the Modern Paradigm of the Scientific and Technological Progress - Ganowicz-Bączyk, Anita (Studia Ecologiae et Bioethicae, 2017)
Environmental ethics finds many of its proponents among philosophizing naturalists. An interesting attitude is presented by Edward Goldsmith, who built biospheric ethics based on the Gaia Hypothesis by James Lovelock. Goldsmith criticizes the Modern scientific paradigm. He perceives it as false and critical-creative for the relation of the humankind with ecosphere. Behind that paradigm states specific ways of understanding progress and particular ontological, axiological, and ethical assumptions (ex. social Darwinism and ethical utilitarianism). Goldsmith calls ethics which covers those convictions technosphere ethics. He submits assumptions of this ethical attitude for criticism and opposes it to biospheric ethics. According to the author, ethics that creates favorable conditions for achieving Gaia’s goals was natural for primitive human societies. These ethics required humans to keep a cosmic order – that is the well-being of individuals as well as the whole community. It assumed to follow an appropriate Way, which depends on respecting definite duties and behavior, especially in the field of rituals and religious life. Therefore, as Goldsmith convinces, one can protect effectively the exospheric order only in a religious way. In his opinion, does not exist more immoral venture than progress, which systematically leads to the replacement of the biosphere by the technosphere. The progress based on the technics leads inevitably to destruction. If we want to survive as a species – we need to return to biospheric ethics.